PERAN CUSTOMER SERVICE DALAM PENINGKATAN KUALITAS PELAYANAN KEPADA PELANGGAN - Risna Haryati; Rina Rostiana (STIA Bagasasi, 2022)
The social development of Indonesian society is currently leading to an information society, namely a society that places telecommunications as a source of activity in carrying out daily activities. The current development into the digital era is a term for the emergence of digital, internet networks, especially computer information technology. The digital era itself is often used to describe digital technology. The Internet has become familiar to people. Nowadays, the internet has become part of our daily needs, as if we can't live without the internet. The problem in this research is how is the role of customer service at PT Solusi Prima Connectivist Bandung? This study aims to see the impact of SOP on customer service. This type of research uses a qualitative research approach and uses descriptive-qualitative types, and uses primary and secondary data. The method of data collection in this research is interviews, observation, and documentation. Then, data processing and analysis techniques were carried out in three stages, namely: data reduction, data presentation, and concluding. The results of the research on the role of customer service in providing services are in two categories, including the basic service strategy, which includes employees on duty in the customer service department, who must be friendly and communicative. Meanwhile, the main service quality includes competence, trust and be trusted, contribution, honesty, social, environmental care and innovation.